Application of RFID on equipment parts readiness management system of semiconductor packaging plant. (1st January 2013) - Wang, Wei-Ling; Huang, Chiao-Tzu; Wang, Shu-Jen; Chang, Chia-Pao; Liao, Hui-Wen
Management of equipment parts readiness for process setup adjustment to meet variable order requirements in a semiconductor packaging plant is crucial to the health of production lines and downtime avoidance. In order to improve the current equipment parts readiness management system, which is exercised by periodical manual verification, this paper propose a RFID-enabled equipment parts readiness management system (REPR-MS) to take advantage of RFID technology in real-time monitor and track the equipment parts readiness flow. To validate the design, four tests of hypotheses were developed to compare the before and after introducing REPR-MS on four different parts flow impacted areas. The hypotheses were tested using survey data originated from a semiconductor packaging plant. This paper studies against the combined pilot run data based on the equipment parts readiness management operation proposed under REPR-MS. Moreover, this paper investigates the production time saving of individual station of the assembly line in the studied plant and the affected rate of average time of each operating step of equipment parts readiness management after introducing REPR-MS. The results show significant potential and promising efficiency for performance improvement and cost saving after adopting REPR-MS.